PERLINDUNGAN HUKUM TERHADAP PIHAK KETIGA (NATUURLIJKE PERSOON) DALAM HUKUM KEPAILITAN TERKAIT ADANYA ACTIO PAULIANA - Indra Kurniawan, I Komang; Dunia, Ngakan Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015, 2015)
This writing is entitled Perlindungan Hukum Terhadap Pihak Ketiga (NatuurlijkePersoon) Dalam Hukum Kepailitan Terkait Adanya Actio Pauliana. The Debitor cannotpay their credits to Creditors that they give a notice of bankruptcy onto the court. It canbe assumed that the Debitor has a not-so-good deed that he transfers the wealth ontothe third party (Natuurlijke Persoon) which results in that the wealth of the Debitorscannot be seized before judgement. This research was purpose to know the role ofCurator on Actio Pauliana and the legal protection for the third party (NatuurlijkePersoon)..The method that was used in this writing was the research method of normativelaws with some approaching based on Constitution point of view.The finding of this research was that the Curators hold a significant role inregulating and settling the Debitor’s wealth of bankruptcy and have rights to proposethe Actio Pauliana. The third party (Natuurlijke Persoon) who had done the law act tothe Debitor of bankruptcy has to restore the objects in the agreement and have rights topropose a legal protection as concuren creditors.
Keywords: bankruptcy, inadvertent, actio pauliana, legal protection